2020
DOI: 10.2147/ott.s255590
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gene Expression Along with Genomic Copy Number Variation and Mutational Analysis Were Used to Develop a 9-Gene Signature for Estimating Prognosis of COAD</p>

Abstract: This study aims to systematically analyze multi-omics data to explore new prognosis biomarkers in colon adenocarcinoma (COAD). Materials and Methods: Multi-omics data of COAD and clinical information were obtained from The Cancer Genome Atlas (TCGA). Univariate Cox analysis was used to select genes which significantly related to the overall survival. GISTIC 2.0 software was used to identify significant amplification or deletion. Mutsig 2.0 software was used to identify significant mutation genes. The 9-gene si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…The mechanism may be that ONECUT1 promotes the proliferation and tumor growth of colorectal cancer cells and promotes liver metastasis by endogenic resistance to anoikis [24]. The high expression of DNAJB13 in colon cancer tissues also con rmed that DNAJB13 is an independent prognostic risk factor for colon cancer patients [25]. The results of the above three genes are consistent with our experiments.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism may be that ONECUT1 promotes the proliferation and tumor growth of colorectal cancer cells and promotes liver metastasis by endogenic resistance to anoikis [24]. The high expression of DNAJB13 in colon cancer tissues also con rmed that DNAJB13 is an independent prognostic risk factor for colon cancer patients [25]. The results of the above three genes are consistent with our experiments.…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism may be that ONECUT1 promotes the proliferation and tumor growth of colorectal cancer cells and promotes liver metastasis by endogenic resistance to anoikis ( Jiang et al, 2019 ). The high expression of DNAJB13 in colon cancer tissues also confirmed that DNAJB13 is an independent prognostic risk factor for colon cancer patients ( Lu et al, 2020 ). The results of the above three genes are consistent with our experiments.…”
Section: Discussionmentioning
confidence: 54%
“…TNM staging of COAD, reflected poor prognosis in COAD ( 26 ). Hence, the remarkable predictive ability of SNHG7 expression suggests its potential as a prognostic biomarker of poor survival in COAD.…”
Section: Discussionmentioning
confidence: 99%